Big Data Analytics Implementation Readiness Among Malaysian Facilities Management Companies - Azlina Md Yassin (Research in Management of Technology and Business, 2023)
Big data analytics (BDA) implementation is under increasing demand in the facilities management (FM) sector. For FM companies, a good grasp of its drivers and difficulties is now necessary due to the increase in its demand. The goal of this study is to pinpoint the factors that influence BDA and implementation readiness among FM companies in Malaysia. This study used quantitative method, where 70 FM companies in Malaysia were polled via questionnaire. Both of the research’s goals were met by using descriptive and correlational analysis as techniques. The outcome demonstrates that FM companies confronted a dearth of knowledgeable staff who had hands-on experience with BDA products. Improving indoor air quality and lowering the chance of important assets failing were determined to be drivers and difficulties that have a significant impact on how ready FM companies are, while the challenges include poor data quality and a lack of competent personnel.